Biodegradable polymeric injectable implants for long‐term delivery of contraceptive drugs. Issue 14 (29th November 2017) - Manoukian, Ohan S.; Arul, Michael R.; Sardashti, Naseem; Stedman, Teagan; James, Roshan; Rudraiah, Swetha; Kumbar, Sangamesh G.
ABSTRACT: Development of injectable, long‐lasting, contraceptive drug delivery formulations, and implants are highly desired to avoid unplanned pregnancies while improving patient compliance and reducing adverse side effects and treatment costs. The present study reports on the fabrication and characterization of two levonorgestrel (LNG) microsphere injectable formulations. Poly(ɛ‐caprolactone) (PCL) with 12.5% and 24% (w/w) LNG were fabricated into microspheres, measuring 300 ± 125 µm, via the oil‐in‐water (o/w) emulsion solvent evaporation technique. Formulations showed sustained drug release up to 120 days. FTIR, XRD, DSC, and TGA confirmed the absence of LNG chemical interaction with PCL as well as its molecular level distribution. The in vitro release of LNG was calculated to be Fickian diffusion controlled and properly characterized. The inclusion of multiple elevated release temperatures allowed for the application of the Arrhenius model to calculate drug release constants and representative sampling intervals, demonstrating the use of elevated temperatures for accelerated‐time drug release studies. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46068. Abstract :